Relationship between self-esteem, social support, and life satisfaction among single mothers in Selangor - Ahmad, Sa’odah; Maznan, Nur Hafizah (Human Resources Management Academic Research Society (HRMARS), 2024)
This study aims to determine the relationship between self-esteem, social support, and life satisfaction among single mothers in Selangor. 360 respondents were obtained from four single mothers associations in Selangor selected through a cluster random sampling technique. A self-administered questionnaire was used for data collection. Rosenberg SelfEsteem Scale (Rosenberg, 1965), Support Functions Scale (SFS) (Dunst et al. 1984), and Life Satisfaction Scale (SWL) Diener, Emmons, Larsen & Griffin, 1985) were used to measure selfesteem, social support, and life satisfaction respectively. The results revealed that more than half of the respondents scored a low level of social support; most of the respondents had a normal level of self-esteem and reported a slight dissatisfaction with their life satisfaction. Social support and self-esteem were positively correlated with life satisfaction. Multiple regression analysis was used to analyze the antecedent and independent variables' relative strength in predicting single mothers’ life satisfaction. It was found that self-esteem was the most important predictor of the respondents’ life satisfaction followed by social support. This study concluded that social support and self-esteem influence the life satisfaction of single mothers. Thus, any effort and intervention to increase single mothers’ life satisfaction must consider these variables.